Boundary value problems for second order elliptic equations - Bitsadze, A. V. (Andrei Vasilevich), 1916-1994 (North-Holland series in applied mathematics and mechanics, 1968)
Applied Mathematics and Mechanics, Volume 5: Boundary Value Problems: For Second Order Elliptic Equations is a revised and augmented version of a lecture course on non-Fredholm elliptic boundary value problems, delivered at the Novosibirsk State University in the academic year 1964-1965. This seven-chapter text is devoted to a study of the basic linear boundary value problems for linear second order partial differential equations, which satisfy the condition of uniform ellipticity.